Schrödinger’s T Cells: Molecular Insights Into Stemness and Exhaustion - Gonzalez, Nancy M.; Zou, Dawei; Gu, Andy; Chen, Wenhao (Frontiers in Immunology, 2021)
T cell stemness and exhaustion coexist as two key contrasting phenomena during chronic antigen stimulation, such as infection, transplant, cancer, and autoimmunity. T cell exhaustion refers to the progressive loss of effector function caused by chronic antigen exposure. Exhausted T (TEX) cells highly express multiple inhibitory receptors and exhibit severe defects in cell proliferation and cytokine production. The term T cell stemness describes the stem cell-like behaviors of T cells, including self-renewal, multipotency, and functional persistence. It is well accepted that naïve and some memory T cell subsets have stem cell-like properties. When investigating the exhaustive differentiation of T cells in chronic infection and caner, recent studies highlighted the stemness of “precursors of exhausted” T (TPEX) cells prior to their terminal differentiation to TEX cells. Clinically successful checkpoint blockades for cancer treatment appear to invigorate antitumor TPEX cells but not TEX cells. Here we discuss the transcriptional and epigenetic regulations of T cell stemness and exhaustion, with a focus on how systems immunology was and will be utilized to define the molecular basis underlying the transition of TPEX to TEX cells. We suggest a “stepwise model” of T cell stemness and exhaustion, in which the loss of stemness and the progression of exhaustion are gradual multi-step processes. We provide perspectives on the research needed to define T cell stemness and exhaustion in the transplantation setting, in which allogenic T cells are also chronically exposed to alloantigens. A better understanding of T cell stemness and exhaustion will shed light on developing novel strategies for immunotherapies.